2020
DOI: 10.1096/fj.201902270r
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone‐androgen receptor: The steroid link inhibiting TRPM8‐mediated cold sensitivity

Abstract: Recent studies have revealed gender differences in cold perception, and pointed to a possible direct action of testosterone (TST) on the cold‐activated TRPM8 (Transient Receptor Potential Melastatin Member 8) channel. However, the mechanisms by which TST influences TRPM8‐mediated sensory functions remain elusive. Here, we show that TST inhibits TRPM8‐mediated mild‐cold perception through the noncanonical engagement of the Androgen Receptor (AR). Castration of both male rats and mice increases sensitivity to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
(118 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, this concentration of testosterone inhibits the TRPM8 activation by menthol. Notably, castration of rats or mice increases their perception of cool temperatures, which was decreased by treatment with testosterone [158]. These results suggest that testosterone decreases sensitivity to cool temperature in sensory neurons through the inhibition of the protein complex between TRPM8 and AR at cell surface.…”
Section: Trpm8 As the Main Target Of The Actions Of Androgensmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, this concentration of testosterone inhibits the TRPM8 activation by menthol. Notably, castration of rats or mice increases their perception of cool temperatures, which was decreased by treatment with testosterone [158]. These results suggest that testosterone decreases sensitivity to cool temperature in sensory neurons through the inhibition of the protein complex between TRPM8 and AR at cell surface.…”
Section: Trpm8 As the Main Target Of The Actions Of Androgensmentioning
confidence: 78%
“…Recently, a similar protein complex between TRPM8 and AR was reported in sensory neurons where it is an important mediator of differences in gender perception of cool temperatures [ 158 ]. This work shows that TRPM8 and AR are located at the cell surface of DRG neurons and that this protein complex is disrupted by the addition of 100 nM of testosterone, inducing AR translocation to the nucleus [ 158 ]. Furthermore, this concentration of testosterone inhibits the TRPM8 activation by menthol.…”
Section: Trpm Subfamily and Steroidsmentioning
confidence: 99%
“…A third non-classical mechanism for TRPM8 regulation by testosterone has been demonstrated in DRG neurons where the androgen receptor and TRPM8 channels form a protein complex in the plasma membrane [120]. High testosterone concentrations (100 nM) inhibit TRPM8 channel activation and the androgen receptor is translocated to the nucleus [120], Figure 4.…”
Section: Nociceptive Trp Channels That Are Targeted By Androgen Actionsmentioning
confidence: 99%
“…A third non-classical mechanism for TRPM8 regulation by testosterone has been demonstrated in DRG neurons where the androgen receptor and TRPM8 channels form a protein complex in the plasma membrane [120]. High testosterone concentrations (100 nM) inhibit TRPM8 channel activation and the androgen receptor is translocated to the nucleus [120], Figure 4. The evaluation of the TRPM8-mediated cold perception performed in castrated mice or rats revealed a decrease in their threshold for mild-cold perception; interestingly, testosterone Testosterone regulates the TRPM8-mediated mild-cold sensitivity.…”
Section: Nociceptive Trp Channels That Are Targeted By Androgen Actionsmentioning
confidence: 99%
“…At nanomolar concentrations, testosterone suppressed TRPM8-mediated currents in native dorsal root ganglion (DRG) neurons and HEK cells co-expressing recombinant TRPM8 and the androgen receptor, but not TRPM8 alone. The study identified a non-canonical signaling pathway downstream of the androgen receptor (AR) activation that involved Src, ERK, and Akt [ 73 ]. In contrast to earlier results, testosterone had no effect on TRPM8 in DRG neurons from AR null mice.…”
Section: Regulation By Phosphorylationmentioning
confidence: 99%